2015
DOI: 10.1186/s12302-015-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the North American signal crayfish (Pacifastacus leniusculus) on European ecosystems

Abstract: As a vector of the crayfish plague (Aphanomyces astaci), invasive crayfish pose a major threat to endemic crayfish species in Europe. But do they affect whole ecosystems and fish species as well? A comprehensive review was done using online search engines on current literature to elucidate possible crayfish effects. It showed that they have the potential to decimate benthic invertebrate populations as well as submerged plants—the first a necessary food source, the second an important part of the habitat of fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In spite of the crayfish plague, Ireland is considered one of the few remaining strongholds for A. pallipes within Europe. One reason for this may be that the invasive signal crayfish ( Pacifastacus leniusculus ), which can cause wide-ranging impacts on freshwater ecosystems and act as a vector for the crayfish plague (Vaeßen and Hollert 2015), has not been reported in Ireland. However, crayfish plague has reached Irish rivers, and large changes in the distribution of A. pallipes have been partially attributed to past plague outbreaks (Demers et al 2005).…”
mentioning
confidence: 99%
“…In spite of the crayfish plague, Ireland is considered one of the few remaining strongholds for A. pallipes within Europe. One reason for this may be that the invasive signal crayfish ( Pacifastacus leniusculus ), which can cause wide-ranging impacts on freshwater ecosystems and act as a vector for the crayfish plague (Vaeßen and Hollert 2015), has not been reported in Ireland. However, crayfish plague has reached Irish rivers, and large changes in the distribution of A. pallipes have been partially attributed to past plague outbreaks (Demers et al 2005).…”
mentioning
confidence: 99%
“…In both cases, the maximum trout density coincides with the absence of mussels. Vaeben and Hollert (2015) showed that the most negative effects of crayfish are related to their increasing density in the riverbed, indicating the need to initiate their immediate removal. Both U. delphinus and A. anatina have undergone an equally intense decline in the Negro River; while both species are frequent in the Alberche River, coinciding with a lower presence of crayfish in the mussel beds.…”
Section: Discussionmentioning
confidence: 99%
“…According to Spanish legislation (Executive order 630/2013), many are considered invasive non-native species (NIS), and are included in the European Union strategy to combat NIS. Two exotic American crayfish (Pacifastacus leniusculus [Dana, 1852] and Procambarus clarkii [Girard, 1852]) are taxa of special concern (EU 1143and EU 1141/2016 as reported by Vaeben and Hollert (2015). In the Iberian Peninsula M. margaritifera (Mm) has not been in contact with crayfish species and thus has no self-protective measures, either active or passive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can affects the trophic chain at all levels, by competing with autochthonous species or predating them and perturbating the entire ecosystem functioning (Loureiro et al, 2015;Jackson et al, 2017;Lang et al, 2020). For example, several studies have shown that P. clarkii (Jackson et al, 2014;Loureiro et al, 2015;Lang et al, 2020), P. leniusculus (Jackson et al, 2014;Vaeßen and Hollert, 2015) and Faxonius virilis (formerly Orconectes virilis) (Jackson et al, 2014) can cause strong decreases in species richness of insect larvae and mollusks through predation after their introductions to a new location. Studies also suggest a decrease in the abundance and diversity of aquatic plants and animals is directly related to crayfish density (Gherardi and Acquistapace, 2007;Rodríguez-Pérez et al, 2015).…”
Section: Geographic Distribution Of the Haplotypesmentioning
confidence: 99%